Clinical Practise Evaluation Quality Improvement Among Nursing Students in The Digital Technology Transformation Era: Literature Review - Muhamad Andika Sasmita Saputra; Tukimin bin Sansuwito; Faridah Mohd Said (Fakultas Kesehatan IKesT Muhammadiyah Palembang, 2023)
Background: Technological developments make the quality of evaluation of clinical practice even better. However, it must be known in advance which technology is more appropriate to use so that evaluation of clinical practice among nursing students can meet the expected quality. Objective: This literature review aims to analyse the efforts that have been made to improve the quality of clinical practice evaluation among nursing students in the digital technology transformation era. Methodology: The literature review uses electronic database sources through journal search engines, Google Scholar, Pro-Quest, PUBMED, and Science Direct. The journal crteria taken were the last five years (2018-2023) using the keywords